Knowledge evolution : expanding organizational intelligence - ALLEE, Verna (Butterworth-Heinemann BostonUS, 1997)
Targets leadership teams who are responsible for developing, implementing, and supporting strategies for enhancing organizational knowledge. Examines the task of managing, creating and building knowledge. Begins by examining today's knowledge era - the new world of instant information and global communication technology - and concludes by discussing innovative practices and processes in current use.